Negotiation of Meaning using Collaborative Learning Tasks on Synchronous Remote Learning - Valverde Solís, Katherine María (2021)
Previous research on classroom-based studies has demonstrated that collaborative learning tasks enable students to engage in the process of negotiating meaning (Foster, 1998; Swain, 2006; Palma, 2014; Masrizal, 2014; Baharun, Harun, & Othman, 2018) to improve their spoken interaction and modified performance. Negotiation of meaning facilitated the development of English as a foreign language (EFL) during face-to-face interactions. However, due to the outbreak of COVID-19, negotiation of meaning has yet to be understood to enhance the students’ communicative interaction on synchronous remote learning. As a qualitative study, it follows an exploratory design to identify how negotiation of meaning operates and impacts the participants’ language development; data gathering methods such as learning tasks, observations, and a interview provided valuable insights on the outcomes of this interactive phenomenon. For this study, three research questions emerged on synchronous remote learning setting to promote and supports the use of collaborative learning tasks as a means of input awareness and linguistic production: (1) how collaborative learning task-type influences Negotiation of Meaning between EFL students, (2) which collaborative task type is more rewarding at fostering Negotiation of Meaning between EFL students, and (3) how the participants’ perspective towards collaborative task type delves into a deeper description of Negotiation of Meaning. Results showed that the development of collaborative learning on a group of eight students at Centro de Estudios en Inglés Conversacional (CEIC), Heredia, Costa Rica, provided students with comprehensible input, increased spoken production, selective attention, and modified output while interacting with each other via Zoom video conferencing.